2019
DOI: 10.1186/s13048-019-0587-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the value of preoperative CYFRA21-1 in the diagnosis and prognosis of epithelial ovarian cancer in conjunction with CA125

Abstract: Growing evidence indicates that the tumor biomarker cytokeratin 19 fragment (CYFRA21-1) is significant for a variety of cancers. However, its role in epithelial ovarian cancer (EOC) has rarely been reported. In this study, a receiver operating characteristic (ROC) curve was utilized to estimate the diagnostic efficiency of CYFRA21-1. The correlation between the CYFRA21-1 level and prognosis was analyzed by Kaplan-Meier survival analysis and univariable and multivariable analyses. The relationship between serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…In addition, KRTs and notably KRT7, KRT18 and KRT19, are widely used to detect circulating tumor cells in the blood or detached tumor cells in ascites [ 46 ]. Soluble protein fragments of keratins, including KRT7, KRT8, KRT18 and KRT19, can be detected in the circulation of cancer patients and are used to monitor disease progression and patient prognostic in certain tumour types [ 46 , 47 , 48 , 49 ]. High level of KRT7 in serum of patients with non-small cell lung cancer complicated with superior vena cava syndrome was associated with a poor prognosis [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, KRTs and notably KRT7, KRT18 and KRT19, are widely used to detect circulating tumor cells in the blood or detached tumor cells in ascites [ 46 ]. Soluble protein fragments of keratins, including KRT7, KRT8, KRT18 and KRT19, can be detected in the circulation of cancer patients and are used to monitor disease progression and patient prognostic in certain tumour types [ 46 , 47 , 48 , 49 ]. High level of KRT7 in serum of patients with non-small cell lung cancer complicated with superior vena cava syndrome was associated with a poor prognosis [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 36 ] It is released into serum during the late S and G2 phases of the cell cycle. [ 37 ] When cells become cancerous, metabolism is enhanced, necrosis is accelerated, and abundant CYFRA21-1 is released into the blood. [ 38 ] Elevated concentrations of serological markers are closely associated with tumor progression and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that combining CYFRA21-1 and CA125 can be used to detect epithelial ovarian cancer. [ 37 ] Patients with head and neck cancer with a high CYFRA21-1 level are more likely to have poor prognosis. [ 41 ] Serum CYFRA21-1 level may also be able to predict NPC.…”
Section: Discussionmentioning
confidence: 99%
“…In this retrospective study, data of 225 patients with OC diagnosed in the a liated Nanchong Central Hospital of North Sichuan Medical College from January 2008 to May 2020 were collected. The inclusion criteria were as follows: (1)all patients underwent primitive surgery under the chief physician; (2) pathological diagnosis was used as the gold standard for assessing the stage of OC, and the pathology reports were obtained after evaluation and issuing by two senior pathologists; (3) the complete blood count and serum CA125 values were collected before initiation of anti-tumor therapy; (4) su cient data could be extracted for the fourfold Table. The exclusion criteria were as follows: patients who had received anti-tumor therapy such as radiotherapy and chemotherapy before the operation, and those that had complications due to other malignant tumors except OC.…”
Section: Patientsmentioning
confidence: 99%
“…Ovarian cancer (OC) is the third most common gynecologic malignancy with high mortality [1]. Owing to the tissue and anatomical characteristics [2], a number of patients are diagnosed with advanced disease (FIGO III-IV, version 2014), by which time it is di cult to achieve optimal debulking surgery (ODS).…”
Section: Introductionmentioning
confidence: 99%